An improved path planning algorithm based on artificial potential field and primal-dual neural network for surgical robot. (December 2022) - Hao, Linjia; Liu, Dongdong; Du, Shuxian; Wang, Yu; Wu, Bo; Wang, Qian; Zhang, Nan
Highlights: The pose of the end-effector can be better controlled by IGPEF. DGC can help solve the local minimum problem. PRF can solve the issues that the robot can not reach the target nearby obstacles. PDNN is used to solve the kinematics problem under safety constraints. RTPVS is applied to prevent the accumulation of position errors. Abstract: Safety and accuracy are essential for path planning in a surgical navigation system. In this paper, an improved path planning algorithm is proposed to increase the autonomous level of spine surgery robots for higher safety and accuracy. Firstly, the dynamic gravitational constant and piecewise repulsion function are adopted to improve the traditional Artificial Potential Field algorithm to solve the common issues of path planning, including local minimum, unable to reach the target near obstacles. To better control the pose of the end-effector in an operation space, the positions of the two endpoints of the end-effector are further constrained. Secondly, an improved Primal-Dual Neural Network with multiple constraints is proposed to minimize the joint angular velocity norm. The multiple constraints are formulated according to the planned path, the obstacle avoidance of the robot and the joint limits. Moreover, a real-time planned velocity scheme is applied to prevent the accumulation of position errors. The simulation results of the pedicle screw implantation demonstrate that the robot can find the collision-free trajectory and arrive at the target position in various complicated situations. More specifically, the error between two endpoints of the end-effector and the target pose is below 0.1 mm in reaching the surgical tool pose, while the maximum position error is around 0.05 mm when performing the planned path. Moreover, two experiments are conducted in the real-world to verify the proposed algorithm is effective in practice.